Quality of Work Life in Family Physicians of Bam, Iran - Mohammad Javad Akbarian Bafghi; Zahra Zare; Narges Rahimi (Tehran University of Medical Sciences, 2020)
Objective: Quality of work life is one of the most important variables recently considered by many managers who seek to improve the quality of their human resources. Considering the vital factor of job satisfaction of family physicians as a service provider, this study was conducted to evaluate the quality of working life of family physicians in Bam. Materials and methods: This research is a cross-sectional and descriptive type. Research population includes all family physicians working at health centers in Bam. The Van Larr Quality of Work Life Questionnaire, which was validated by Nekoei Moghadam, was used. The questionnaire data is analyzed by SPSS 24 from statistical-descriptive tests (mean and standard deviation) and T-test and ANOVA. Results: Quality of work life score in family physicians is obtained 2.93 out of 5. Control ambiance in work (CAW) has the highest mean (3.16) and Work-life balance (WLB) has the lowest mean (2.29). Work experience has a meaningful relationship just with the two components of WLB and SAW in Quality of work life (p = 0.036). Furthermore, in the factor of GWB, the average score of unmarried physicians (Mean = 3.18) were more than the married ones (Mean = 3.05) (p = 0.010). The mean score of unmarried physicians was more than the married ones. Conclusion: The quality of work life from the family physicians is about upper-intermediate. Thus, authorities of the family physician concept in the ministry of Health, and also in the Bam city should pay more attention to the family physician's work life and consider programs and solutions in order to improve it.